Vitamin C inhibited FasL-induced apoptotic death of mouse dendritic cells through c-FLIP expression - Xuan, Nguyen Thi; Thu Hien, Le Thi (Vietnam Journal of Biotechnology, 2020)
Vitamin C (VitC) is a potent antioxidant and contributes as an apoptosis inhibitor by preventing death receptor-triggered caspase 8 activity. Fas ligand (FasL) induces the apoptotic cell death via activation of Fas signaling, which is dependent on the expression level of anti-apoptotic molecule c-FLIP (FADD-like IL-1beta-converting enzyme-inhibitory proteins). The present study addressed the effects of VitC on survival of dendritic cells (DCs), a regulator of innate and adaptive immunity. To this end, mouse bone marrow cells were isolated and cultured to attain bone marrow-derived DCs (BMDCs). The cells were treated with FasL in the presence or absence of VitC. Real time RT-PCR, Western blotting and FACS analysis were performed to determine different hallmarks of DC apoptosis. As a result, FasL treatment resulted in activation of caspase 8 and stimulation of cell membrane scrambling, the effects were supressed when VitC was present in the cell culture or the cells were transfected with FLIP siRNA. In conclusion, VitC prevented FasL-triggered DC apoptosis mediated through the expression of c-FLIP.